Who should own public science? Preprints, power, and publishers - Tennant, Jon (Septentrio Conference Series, 2018)
Watch the VIDEO. What is Open Science? When we talk about it, we use technical terms like transparency and reproducibility, or use personal principles like fairness, equality, or justice. But aren’t these just traits of "good" science, conducted by humans with a good ethical purpose? Shouldn’t this be all science..? The problem is that in the present system we aren’t rewarded for doing good science, and academia has become a bit Game of Thrones-y. Almost every conversation about progressing scholarly communication comes down to one thing: Research evaluation and career progression. Researchers are just like everyone else, and aware of the risks associated with driving on the wrong side of the road. Modern research culture tells us not to innovate, not to question, and not to push boundaries. It is perversely non-traditional, and the system is defined by inertia, fear, and skewed power dynamics. How can we all work together to kick-start a new culture of ‘open’ scientific practices, without putting our best and brightest at risk? How do we want people in the future to remember this pivotal time in the history of science? What is the future system that we want students to inherit, and how can we build a path towards that today?